Estudio agrosocioeconómico de pequeños productores de maíz (Zea mays L.) en el recinto Aguas Frías del Cantón Ventanas, Provincia de Los Ríos. - Cedeño Mora, Noely Jomira (2019)
Corn cultivation is the most representative in the Aguas Frías enclosure of the Ventanas canton, however, small farmers face many economic and productive problems. The research aimed to evaluate small corn producers and their contribution to the economic well-being of families. The surveys were carried out on 25 maize producers from the Aguas Frías site of the Ventanas canton, made up of closed questions according to the research objectives. Surveys were conducted on 25 maize producers in the study area. The results showed that the majority of producers own their own home (cement or mixed), consuming water from wells, rivers, estuaries or slopes, they grow corn on their own land, as well as rented, depending on between one to three people of the maize activity in the farm, maintaining a weekly income that fluctuates between 101 to 150 dollars per week. The main services that all respondents access is electric power and mobile telephony, with paid television, public lighting, internet, a few are close to educational establishments and health center, while no farmer has fixed telephony, drinking water, sewerage. In the farms visited, agricultural activity predominates, sowing up to a maximum of 3 hectares, evidencing that Advanta 9313 is the most profitable seed. The most commonly used seeds are Emblem 777, Somma, Advanta 9313, Hercules and Thunder, being limited the use of machinery for planting, pump spraying, use of scythes, as well as for harvesting, while they do use it for shelling either own or rented, also mostly lacking irrigation. The majority of corn producers sell in commercial houses and in collection centers, the main problem being low prices and the lack of buyers, whose transportation is done in sacks, with payment is cash and credit 15 days after the sale, destined to the national and local market. Keywords: Corn cultivation, corn hybrids, socioeconomic analysis